Micro-credit, risk coping and the incidence of rural-to-urban migration - Quamrul Ahsan (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
The focus of this paper is on the rural poor of south Asia and their struggle to cope with the seasonal risk of unemployment and the ensuing income risks. In the absence of formal credit or insurance markets the rural poor typically resort to, among other options, the following informal strategies to cope with seasonal income risks: (i) seasonal rural-to-urban migration, and (ii) mutual (ex-post) transfers between families of friends and relatives. Access to credit through a microfinance institution could also provide a competing source of insurance. The question raised in this paper is how the access to credit may affect the more traditional/time honoured means of risk coping, such as seasonal migration. Given that credit, i.e., a creditfinanced activity, is potentially a substitute for seasonal migration, it is reasonable to argue that easy access to credit (or high return on credit) will lower the incidence of migration. However, there also exists a potential complementarity between the two activities (if implemented jointly) in terms of gains due to diversification of income risks. That is, given that income from migration is not typically subject to the same shocks as income generated by a credit-financed activity, a joint adoption of both activities creates opportunities for diversification of risk in the family incomes portfolio. If the diversification gains are large enough then the adoption of both activities jointly will be preferred to adopting either of the activities individually. In that event, introduction of microfinance in rural societies may result in raising the incidence of migration. The joint adoption case for rural households is modelled using a choice theoretic framework, and exact conditions are derived for when joint adoption is preferable to adoption of a single project. The model of joint adoption is estimated by applying a Bivariate Probit regression model on a single cross-section of household survey data from rural Bangladesh. Our preliminary results show that indeed the probability of participation in migration by household members is positively related to the probability of the household being a credit recipient.
Keywords: J43; Q12; D81; D1; O1; J61; R23; 330; Development; South Asia; Poverty; Microfinance; Rural labour markets; Rural-to-urban migration; Risk-coping strategies